Pengembangan Sistem Informasi Berbasis Website bagi BUMDES Sedarum Nguling Pasuruan - Siroj Alhadi, Muhammad; Rosyidi, Khafizh; Putri Lestari, Alifia; Qurrota A’yunina, Laila (Humanist Journal, 2024)
Awareness of the importance of information technology today makes Sedarum Village need an integrated information system, especially in the management and efforts to develop BUMDes in a sustainable manner. An information system that is built and maintained properly will provide tangible benefits which can be factually seen through the income earned and costs incurred. An indicator of success that has an impact on the development of BUMDes is increasing business productivity. The method used is the prototyping approach methodology, where prototyping is part of the software development method in the form of a physical model of the performance of a system that serves as an initial model of an information system. Through this prototyping method a model will be produced in the form of an information system prototype as a liaison between developers and users to interact in an effort to develop an integrated information system.